Predictors and Factors Associated with Insomnia in a Brazilian Sample: A Cross-Sectional Study - Aizawa, Isabela Mayumi Nishino; Alckmin-Carvalho, Felipe; Soares Filho, Helder Sergio Lira; Hasan, Rosa; Toscanini, Andrea Cecilia; El Rafihi-Ferreira, Renatha (Sleep Science, 2025)
Chronic insomnia is associated with various functional and mental health impairments. The present study aimed to evaluate variables potentially associated with insomnia in a Brazilian sample.The study was conducted in a psychiatric hospital of a public medical school in the city of São Paulo, Brazil. The sample included 1,435 adults with a mean age of 38.3 years. Participants were divided into two groups: one with individuals diagnosed with insomnia (according to the Diagnostic and Statistical Manual of Mental Disorders, 5th edition and the Insomnia Severity Index) and a comparison group without the diagnosis. The Hospital Anxiety and Depression Scale (HADS) was used to assess psychopathological variables (anxiety and depression) and sociodemographic and anthropometric questionnaires to provide further characterization of the sample. Multivariable binary logistic regression analyses were performed.Male sex and lacking a university degree were associated with increased odds of insomnia, with average increases of 1.93 and 1.89, respectively. Each additional year of age and each additional point on the depression and anxiety increased the likelihood of insomnia by averages of 1.05, 1.18, and 1.40, respectively.This study provides evidence of associations between biopsychosocial factors and insomnia, suggesting the potential for developing preventive and treatment protocols for this condition.
Keywords: insomnia; mental health; psychopathology; sleep deprivation; patient health; anxiety and depression